ASPECTS CONCERNING THE PUBLICITY OF MOVABLES AND IMMOVABLES IN THE MARITIME FIELD - Marilena MARIN (Challenges of the Knowledge Society)
This document presents elements of publicity for a specific category of goods, namely, ships. It also analyzes the recording and registration of Romanian flag ships. Each of these items requires special procedures, depending on the operation recorded where the ship is registered. The registration of ships under construction and especially of Romanian flag ships, the granting, suspension and withdrawal of the right to navigate under the Romanian flag, the registration and removal of ships from records, the acquisition, transmission, transcription and extinction of real rights and/or obligations regarding ships and the procedure for issuance, extension of validity and renewal of the nationality documents require compliance with certain procedures. The present article may interest professionals concerned with these notions that are often met in maritime law and, to a lesser extent, in common law.